Risk stratification of oxaliplatin induced peripheral neurotoxicity applying electrophysiological testing of dorsal sural nerve. - Cavaletti, Guido; Alberti, Paola; Cazzaniga, Marina E.; Cortinovis, Diego; Rossi, Emanuela; Valsecchi, Maria G.; Argyriou, Andreas A.; Kalofonos, Haralabos P.; Briani, Chiara; Campagnolo, Marta; Cacciavillani, Mario; Bruna, Jordi; et al. (Supportive Care in Cancer, 2018)
Purpose: We aimed to verify the predictiveness of dorsal sural nerve neurophysiological monitoring in obtaining risk stratification for oxaliplatin-induced peripheral neurotoxicity (OXAPN).Methods: We conducted a secondary analysis on a cohort of 110 colorectal cancer patients who were evaluated clinically and neurophysiologically before chemotherapy, at mid-treatment and at discontinuation. We applied the classification tree analysis method to predict the end-of-treatment OXAPN neurophysiological diagnosis, using data recorded at mid-treatment. We then ascertained the correlation between the obtained classes and neurological impairment at the end of treatment (Fisher's exact test).Results: Dorsal sural nerve monitoring enabled us to stratify oxaliplatin-treated patients into risk classes with an implemented approach to neurophysiology application in this setting. Neurological outcome at discontinuation was predicted by neurophysiological monitoring performed during chemotherapy administration.Conclusions: We demonstrated the role that neurophysiology may play in clinical trials as an early surrogate marker that can predict OXAPN development at the end of treatment. Specifically, we propose abnormal dorsal sural sensory nerve testing as an early biomarker in identifying patients at high risk of eventually developing OXAPN.